2015
DOI: 10.1002/adsc.201401163
|View full text |Cite
|
Sign up to set email alerts
|

Very Important Publication: Iridium‐Catalyzed Intramolecular Enantioselective CH Alkylation at the C‐2 Position of N‐Alkenylindoles

Abstract: Intramolecular enantioselective alkylation of N-alkenylindoles proceeded via C À H bond cleavage at the C-2 position in the presence of a cationic iridium catalyst with a diphosphine ligand. Aroyl groups at the C-3 position of the indoles operated as effective directing groups, and chiral 1-substituted-2,3-dihydro-1H-pyrrolo[1,2-a]indoles were obtained in high yield with excellent ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 46 publications
(8 reference statements)
1
23
0
Order By: Relevance
“…Intramolecular C−H bond functionalization often proves to be very advantageous for manufacturing heterocyclic motifs with fused ring system by stitching a molecular unit with desirable regioselectivity . In this context, various research groups have reported the Rh, Ru, Ir, and Co‐catalyzed, directed intramolecular hydroarylation of olefin‐tethered arenes to synthesize several carbo and heterocycles . The Park and Glorius groups, also described a Rh and Co‐catalyzed intramolecular hydroarylation reaction of alkyne‐tethered hydroxamic esters.…”
Section: Figurementioning
confidence: 99%
“…Intramolecular C−H bond functionalization often proves to be very advantageous for manufacturing heterocyclic motifs with fused ring system by stitching a molecular unit with desirable regioselectivity . In this context, various research groups have reported the Rh, Ru, Ir, and Co‐catalyzed, directed intramolecular hydroarylation of olefin‐tethered arenes to synthesize several carbo and heterocycles . The Park and Glorius groups, also described a Rh and Co‐catalyzed intramolecular hydroarylation reaction of alkyne‐tethered hydroxamic esters.…”
Section: Figurementioning
confidence: 99%
“…Shibata and co‐workers reported an additional application of Ir‐catalyzed, enantioselective alkylation in the synthesis of tricyclic indoles 72. The protocol exploited a cationic Ir complex and a chiral phosphine ligand to afford the 5‐ exo ‐products in mostly good yields and in excellent ee s in most cases (Scheme ).…”
Section: Ch Activation At the C‐2 Position Of The Indole Frameworkmentioning
confidence: 99%
“…[72] Thep rotocole xploited ac ationic Ir complex and ac hiral phosphine ligand to afford the 5-exo-products in mostly good yields and in excellent eesi nm ost cases( Scheme 27).…”
Section: Scheme18mentioning
confidence: 99%
“…Reaction Coupling partner/reagent Catalyst References 1a rylation aryl halides Rh [25] 2P d [26,27,[31][32][33] 3a renes Pd [28][29][30] 4d iaryliodoniumsalts Pd [33,35] 5a rylboronr eagents Pd [36][37][38] 6R h, Ru [39,40] 7a rylsilanes Rh [41] 8P d [42] 9b enzoic acid Rh [43] 10 alkynylationa lkynes Pd [44] 11 alkenylationP d [46,[50][51][52]54,55] 12 alkenes Rh [48,53,59] 13 Ru [53b,60] 14 vinylcarboxylic acids Rh [61] 15 Ru [49] 16 alkynes Fe [56] 17 Co [58] 18 alkylation alkyl halides Pd [63,65] 19 Co [66] 20 Pd [70] 21 Fe [56] 22 alkenes Ir [67,71] 23 Co [69] 24 Ir [72] 25 acylationa ldehydes Pd [75] 26 Rh [76] 27 annulations Co [57] 28 Pd [77,…”
Section: Entrymentioning
confidence: 99%